KAJIAN PELELANGAN KONSTRUKSI BERDASARKAN KEPPRES 80/2003 DAN PERPRES 54/2010 (Studi Kasus : LPSE Universitas Diponegoro) - Nur Wakhid; Wahyu Kuncoro; M. Agung Wibowo; Hari Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Construction sector has an important role in increasing economic growth. To create a condition that all necessary infrastructure that can guarantee an increase in economic activity. Procurement of facilities and infrastructure as well as the government's infrastructure, using the budget of income and expenditure (APBN/APBD). To supervise the use of budget, procurement regulations are arranged Keppres 80/2003 and amended by Perpres 54/2010. The tender process is expected to use electronic media (e-procurement) to be more transparent, accountable, effective and efficient, in line with efforts to eradicate corruption, collusion and nepotism. The method of research used descriptive research. The sampling technique used purposive sampling with data taken from Diponegoro University 2 LPSE and questionnaires to the respondents as service providers, service users, and the auction committee. A descriptive analysis of data processing and data processing using a Likert scale questionnaire on the subject of the study variables. The results of comparative analysis based on the tender for the construction of Perpres 54/2010 is better than the Keppres 80/2003.In terms of the duration of the execution of the auction package is based on Perpres 54/2010 1.76 is faster, there was the time efficiency of 50%. The cost, Perpres 54/2010 is cheaper. In the case of list requirements, both rules have the same relative terms. In terms of accuracy in the selection of service providers in the Perpres 54/2010 be better. In terms of selection of participants is more stringent Perpres 54/2010 instead of Presidential Decree 80/2003. In terms of transparency in the determination of winners, that the new regulations more transparent. General opinion of the regulation services provider 54/2010 is better.